Upscaling the livelihood of smallholders through adoption of ‘Maudamani’ super rice variety - Mishra, S K; Das, Lipi; Bisen, J P; Mondal, B; Pradhan, S K; Lenka, S; Satapathy, B S; Dash, S S (Indian Farming, 2021)
In Indian subcontinent, rice is not only an important food for natives but is the way of life itself.In India more than 80% of the farmers are marginal and small and about 56% of the farmfamilies are engaged in rice cultivation which provides livelihood options to 40% of the rural poor.However, the meagre productivity of rice is one of the prime factors for distress which has directconnotation with their livelihood. Therefore, the strategy will have to upscale the smallholders inaspects in which they have skills and have direct bearing on their livelihood. In this context,technological options available to ensure a respectable livelihood to smallholders are discussed.